The intention to use e-money transaction in Indonesia based on TAM and TPB Concept - Khatimah, Husnil; Halim, Fairol (Asia-Pacific Institute of Management, 2014)
The aim of this paper is to determine the intention of customer to use electronic money transaction (e-money).Electronic money is new technology that is exists for electronic transaction.The issue appears that is a potential for crime for the customer bring a lot of money to the Bank and in Indonesia, the electronic money is still not optimal where majority the customer prefer to use Cash or go to ATM.E-money is a stored value or prepaid products that had recorded the finds or value and it can be done in online and offline transaction.Behavioural intention is a process in any type of actual behaviour with giving the expression in making decision to the adoption of behavioural intention.It attempts to examine the intention to use e-money and extended Technology Acceptance Model (TAM) and Theory Plan Behavioural (TPB) on the Behavioural Intention(BI) to use the e-money transaction.The conceptual@amework of e-money transactions were reviewed to understand behavioural intention of consumers@om perceived usefulness, perceived ease of use, perceived risks, perceived behavioural intentions, security and privacy.The proposed@amework and hypotheses were presented in this article.Quantitative method will be utilised as sources of data collection.A total of one thousand and five hundred respondents will be selected using convenient sampling method in Padang, Indonesia.Descriptive analysis and Multiple Regression analysis will be conducted to analyse the data.The article ended with suggestion for future studies.